2019
DOI: 10.3847/1538-4357/ab40b9
|View full text |Cite
|
Sign up to set email alerts
|

“Double-tracking” Characteristics of the Spectral Evolution of GRB 131231A: Synchrotron Origin?

Abstract: The characteristics of the spectral evolution of the prompt emission of gamma-ray bursts (GRBs), which are closely related to the radiation mechanism (synchrotron or photosphere), are still an unsolved subject. Here, by performing the detailed timeresolved spectral fitting of GRB 131231A, which has a very bright and well-defined single pulse, some interesting spectral evolution features have been found. (i) Both the low-energy spectral index α and the peak energy E p exhibit the "flux-tracking" pattern ("doubl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

5
3

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 99 publications
1
42
0
Order By: Relevance
“…So far, this tracking behaviour has only been found in a few GRBs, i.e. in GRB 131231A (Li et al 2019) and GRB 140102A (Gupta et al 2021b), the low energy spectral index remains in the synchrotron limit (𝛼 𝑝𝑡 = −2/3). Similarly, in the case of GRB 190530A, 𝛼 pt values are within the synchrotron limits for the first two pulses.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…So far, this tracking behaviour has only been found in a few GRBs, i.e. in GRB 131231A (Li et al 2019) and GRB 140102A (Gupta et al 2021b), the low energy spectral index remains in the synchrotron limit (𝛼 𝑝𝑡 = −2/3). Similarly, in the case of GRB 190530A, 𝛼 pt values are within the synchrotron limits for the first two pulses.…”
Section: Discussionmentioning
confidence: 92%
“…The 𝛼 pt also evolves with time but does not display any typical trends (Crider et al 1997). Recently, Li et al (2019) and Gupta et al (2021b) found that both 𝐸 p and 𝛼 pt track flux ("double-tracking") for GRB 131231A and GRB 140102A.…”
Section: Introductionmentioning
confidence: 99%
“…To test the applicability of our calculations, we perform theoretical modeling of two representative short GRBs, i.e., GRB 110529A (intensity-tracking) and GRB 090227B (hard-to-soft) respectively. The data used from Fermi-GBM 2 is analyzed with the standard Bayesian approach and the time bin selection method to obtain the time-resolved spectra (see details in Li et al 2019). Because of the huge computational cost in each calculation and potential strong degeneracy between the parameters, a strict fitting procedure with the Bayesian method is not carried out in the current work.…”
Section: Application To Grb Datamentioning
confidence: 99%
“…Thus α may not be a good indicator to justify the radiation mechanism (Burgess et al 2015;Iyyani et al 2015;Meng et al 2018). It was found that there are two distinct evolution patterns for E p , i.e., hard-to-soft (Norris et al 1986) and intensity-tracking (Golenetskii et al 1983;Bhat et al 1994;Kargatis et al 1994;Ford et al 1995;Preece et al 2000;Lu et al 2010;Ghirlanda et al 2011;Lu et al 2012;Li et al 2019. In addition, Hakkila & Preece (2011) show that all single pulses GRBs could have the hard-to-soft evolution pattern.…”
Section: Introductionmentioning
confidence: 99%
“…After decades of researches, the radiation mechanism of GRB prompt emission is still unclear (e.g., Zhang & Yan 2011;Geng et al 2018Geng et al , 2019Lin et al 2018;Zhang et al 2018aZhang et al ,b, 2021Duan, & Wang 2019a,b;Huang et al 2019;Li et al 2019b;Yang et al 2020;Zhang 2020). The photospheric emission model seems to be a promising scenario (e.g., Abramowicz et al 1991;Thompson 1994;Mészáros & Rees 2000;Rees & Mészáros 2005;Pe'er & Ryde 2011;Fan et al 2012;Lazzati et al 2013;Ruffini et al 2013;Gao & Zhang 2015;Bégué & Pe'er 2015;Pe'er et al 2015;Ryde et al 2017;Acuner & Ryde 2018;Hou et al 2018;Meng et al 2018Meng et al , 2019Li 2019a,c,d;Acuner et al 2020;Wang et al 2020).…”
Section: Introductionmentioning
confidence: 99%